Necessity of Immobilizing the Metacarpophalangeal Joint in Carpometacarpal Osteoarthritis: Short-Term Effect - Cantero-Téllez, Raquel; Valdes, Kristin; Schwartz, Deborah A; Medina-Porqueres, Iván; Arias, Jean-Christophe; Villafañe, Jorge Hugo (Sage Journals, 2018)
Conservative treatment for carpometacarpal (CMC) joint osteoarthritis (OA) may include orthotic fabrication to decrease pain. Different types of orthoses have been used as conservative interventions to improve symptoms, but there are no guidelines specifying if inclusion of the thumb metacarpophalangeal (MCP) in an orthosis is required in the treatment of thumb CMC joint OA. The main objective of this study is to determine the effectiveness of 2 different thumb CMC joint orthotic designs on pain reduction and improved hand function: one design immobilizes both the MCP joint and the CMC joint and the other design immobilizes only the CMC joint. Methods: A total of 66 patients were included in the study. One group of 33 patients received a short thumb orthosis with the MCP joint excluded, and the other group of 33 patients received a short thumb orthosis with the MCP joint included. Outcomes measures included the visual analog scale for pain and the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH; Spanish version) for function. Results: In both patient groups, the orthoses contributed to decreased pain levels and improved functional abilities (F1.0 = 315.467 and F1.0 = 72.419; both, P < .001). There was no significant difference between the 2 groups regarding pain or improvement in daily activities (F1.0 = 0.553 and F1.0 = 2.539; both, P > .05). Conclusion: There are benefits of either thumb orthotic design on pain reduction and functional improvement even after 1 week of using the orthoses as the sole conservative treatment.
Keywords: Artrosis; Articulaciones - Enfermedades; Carpometacarpal joint; Hand function; Osteoarthritis; Thumb orthoses; Thumb pain